2019
DOI: 10.1017/s1478951519000397
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care for older South Asian migrants: A systematic review

Abstract: AbstractObjectiveSouth Asian migrants have a higher burden of life-threatening diseases and chronic diseases compared to other ethnic groups. Yet, knowledge gaps remain around their palliative care needs in the host countries. The aim of the review was to present results from a systematic literature review of available international evidence on experiences with and perspectives on palliative care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
(291 reference statements)
1
9
0
2
Order By: Relevance
“…The findings of this review are both consistent with and complementary to themes found elsewhere on migrants' PC in Europe and internationally [19,23,60,61]. Articles included in the current review discuss more explicitly the challenges at an individual level) rather than how economic and/or structural factors influence the utilization of PC among migrants.…”
Section: Discussionsupporting
confidence: 77%
“…The findings of this review are both consistent with and complementary to themes found elsewhere on migrants' PC in Europe and internationally [19,23,60,61]. Articles included in the current review discuss more explicitly the challenges at an individual level) rather than how economic and/or structural factors influence the utilization of PC among migrants.…”
Section: Discussionsupporting
confidence: 77%
“…Algunos estudios reflejan que los cuidados recaen sobre todo en las figuras femeninas del sistema familiar (Shabnam et al, 2020).…”
Section: ▪ El Rol De La Familia En Los Cuidadosunclassified
“…En la toma de decisiones, las personas confían en la toma de decisiones compartidas con otros miembros de la familia, a menudo el hijo mayor (Shabnam et al, 2020) o el cónyuge (Khosla et al, 2019) es quien asume este rol. En las culturas sudasiáticas, a diferencia de las occidentales, la centralidad de las decisiones no está en la autonomía del individuo, sino el foco es la familia vista como un todo en el que se unen todos los miembros (Khosla et al, 2019).…”
Section: ▪ El Rol De La Familia En Los Cuidadosunclassified
“…Overcoming language barriers is crucial in regard to patients' rights and when achieving informed consent is needed. Systematic review of 30 articles pointed out three main themes: "palliative care practice within the family, trust as a precondition of palliative care, and the importance of knowledge and cultural competency" (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Palliative Care For Migrants In General Practicementioning
confidence: 99%